Efeitos do hipotireoidismo na neuropatia periféricaexperimental por constricção crônica do nervoisquiático de ratos - Sousa, Kalina Kelma Oliveira (2017)
Thyroid hormones are active participants in the growth of cell differentiation and in the metabolism of the organism, being essential for somatic and neural development. The absence of these hormones in the central and peripheral nervous system results in pathological conditions, such as the reduction of dendritic tree development, the number of axon-dentrite synapses, and cause myelinization defects. Neuropathic pain is caused by neural damage, characteristic of peripheral neuropathy, common in the neurological clinic, and has been studied by several researchers. However, the events and modifications that may occur in peripheral neuropathy during hypothyroidism are still poorly studied. In the context of the importance of hormones for the development of the nervous system, the present study was designed to understand the effects of hypothyroidism on experimental neuropathy induced by chronic constriction of the sciatic nerve (CCI) in rats, evaluating nociceptive behavior and aspects Morphological and neurochemical effects of neural damage. Method: Hypothyroidism was induced in male Wistar rats, weighing between 200 and 250g, by daily consumption of propylthiauracil (PTU) in drinking water at 0.05%, and weighed weekly for 6 weeks, peripheral neuropathy was induced by injury By chronic constriction (CCI) in the sciatic nerve of rats, using the Bennet and Xie model, in the 3rd week of PTU use, hypothyroidism was confirmed by blood thyroxine (T4) in the orbital plexus. For the evaluation of neuropathic pain the animals were submitted to the mechanical plantar hyperalgesia test, using electronic Von Frey, before induction of hypothyroidism and after CCI, for three weeks (21 days). Later, the animals were euthanized and the thyroid, the sciatic nerve and the dorsal root ganglion were removed. The histological analysis of the thyroid gland was performed by the hematoxylin and eosin (HE) staining method, and its measurements were performed through a pachymer. The morphometric analysis by immunofluorescence of the myelin basic protein (PBM) in the sciatic nerve, the activation transcription factor 3 (ATF-3) and the onco-transcription gene (c-Fos) in the dorsal root ganglia (GRD) , to assess neuronal damage and alteration of the activity of these markers in hypothyroidism and peripheral neuropathy. Electron microscopy was performed on the sciatic nerve and measurements of area and diameter of the fibers were analyzed. Differences were assessed using Student's t-test and ANOVA with p <0.05. Results: Hypothyroidism and hypothyroid and neuropathic groups (HYP + CCI) showed reduction of thyroxine up to the third week, did not gain weight during the six weeks, presented increase in thyroid measurements, alteration in follicular shape and hyperplastic cells , Compared to control; In the GRD presented increased c-Fos immunoexpression compared to the control and decrease of the ATF-3 immunoexpression compared to the neuropathic group (CCI) in the sciatic nerve; The CCI, HYP and HYP + CCI groups showed increased immunoexpression of PBM in relation to the control group. The HYP group presented an increase in the paw withdrawal threshold while the CCI and HYP + CCI decrease compared to the control, the HYP + CCI group the threshold was higher in relation to the CCI. The histological and morphometric analysis of the nerve in the HYP group presented vacuolar demyelination in HE and alterations in the myelin sheath, decrease in the diameter of small and medium caliber fibers and increase of the area of the axons compared to the control. Conclusion: Our data demonstrated that in hypothyroidism there is an increase in pain threshold and also associated with peripheral neuropathy; the markers of pain and neural regeneration are altered in the DRG and in the sciatic nerve there are morphological alterations in the suggestive of a Wallerian degeneration.